The Hypolipidemic Effect of Dalbergia odorifera T. C. Chen Leaf Extract on Hyperlipidemic Rats and Its Mechanism Investigation Based on Network Pharmacology. (27th December 2021) - Mei, Hui; Hu, Huiming; Lv, Yanni; Ma, Guangqiang; Tang, Fangrui; Hong, Zhou; Shao, Feng
Abstract : Objective . The aim of this study was to explore the hypolipidemic effect and mechanism of Dalbergia odorifera T. C. Chen leaf extract. Methods . The hypolipidemic effect of D. odorifera leaf extract was investigated using a hyperlipidemic rat model. Then, its mechanism was predicted using network pharmacology methods and verified using western blotting. Results . Compared with the levels in the model group, the serum levels of triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) decreased significantly, whereas the serum level of high-density lipoprotein cholesterol (HDL-C) increased dramatically after treatment with the extract. The degrees of hepatocyte steatosis and inflammatory infiltration were markedly attenuated in vivo. Then, its hyperlipidemic mechanism was predicted using network pharmacology-based analysis. Thirty-five key targets, including sterol regulatory element-binding protein cleavage-activating protein (SCAP), sterol regulatory element-binding protein-2 (SREBP-2), 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), low-density lipoprotein receptor (LDLR), and ten signaling pathways, were associated with hyperlipidemia. Finally, it was verified that the extract downregulated the protein levels of SCAP, SREBP-2, and HMGCR, and upregulated protein levels of LDLR. Conclusion . These findings provided additional evidence of the hypolipidemic effect of D. odorifera leaf extract.